2023
DOI: 10.15252/emmm.202216987
|View full text |Cite
|
Sign up to set email alerts
|

sTREM2 is associated with amyloid‐related p‐tau increases and glucose hypermetabolism in Alzheimer's disease

Abstract: Microglial activation occurs early in Alzheimer's disease (AD) and previous studies reported both detrimental and protective effects of microglia on AD progression. Here, we used CSF sTREM2 to investigate disease stage‐dependent drivers of microglial activation and to determine downstream consequences on AD progression. We included 402 patients with measures of earliest beta‐amyloid (CSF Aβ1‐42) and late‐stage fibrillary Aβ pathology (amyloid‐PET centiloid), as well as sTREM2, p‐tau181, and FDG‐PET. To determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 63 publications
(105 reference statements)
1
15
0
Order By: Relevance
“…This finding contrasts with previous literature showing a link between sTREM-2 and FDG-PET signal in AD patients with Mild Cognitive Impairment (MCI). Biel and colleagues reported that sTREM-2 positively associates with FDG-PET hypermetabolism in patients with CSF findings of amyloidopathy but negative amyloid-PET, while, in case of amyloid-PET positivity—reflecting higher levels of fibrillary Aβ—sTREM-2 associates with hypometabolism instead [ 33 ]. Nevertheless, this discrepancy could be due to our limited sample size and to the different clinical and AT profiles of our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding contrasts with previous literature showing a link between sTREM-2 and FDG-PET signal in AD patients with Mild Cognitive Impairment (MCI). Biel and colleagues reported that sTREM-2 positively associates with FDG-PET hypermetabolism in patients with CSF findings of amyloidopathy but negative amyloid-PET, while, in case of amyloid-PET positivity—reflecting higher levels of fibrillary Aβ—sTREM-2 associates with hypometabolism instead [ 33 ]. Nevertheless, this discrepancy could be due to our limited sample size and to the different clinical and AT profiles of our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works also investigated the relationship between measures of cerebral glucose consumption and some markers of neuroinflammation, focusing especially on pre-symptomatic or very early AD, highlighting the presence of higher 18 F-FDG-PET uptake in relation to neuroinflammatory processes in early AD [ 31 , 32 , 33 ]. We aimed to implement these findings by evaluating a cohort of symptomatic patients diagnosed with sporadic AD, by exploring possible correlations between regional hypometabolism of 18 F-FDG-PET and changes in CSF biomarkers of microglial and astrocytic reactivity (sTREM-2, GFAP and β-S100).…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Elevated CSF sTREM2 was also related to attenuated brain atrophy, glucose hypometabolism, and cognitive decline. 19,[21][22][23][24] However, one recent study reported the accelerated effects of CSF sTREM2 and microglial activation on future tau deposition. 25 Supporting this, CSF sTREM2 has also been linked to Aβ-related tau aggregates.…”
mentioning
confidence: 99%
“…25 Supporting this, CSF sTREM2 has also been linked to Aβ-related tau aggregates. 24,26 Together, the roles of TREM2-dependent and PGRN-dependent microglial reactivity in the course of AD remain controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation